2018
DOI: 10.15171/apb.2018.003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the Potential Ocular Inserts by Electrospinning Method to Achieve the Prolong Release Profile of Triamcinolone Acetonide

Abstract: Purpose: The poor bioavailability of drugs in the ocular delivery systems is an important issue and development of delivery systems with prolonged release profile could be in a major importance. This study aims to develop an ocular delivery system using electrospun nanofibers to be a candidate insert for delivery of triamcinolone acetonide.Methods: For this purpose, three different chitosan-based formulations were prepared by electrospinning method, and electrospun nanofibers were compared to a formulation com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The determined average of zeta potential of the nanofibers was -13.5 ± 0.17 mV (Figure 3), indicating fiber stability being the repulsive charge between the fibers enough to avoid agglomeration [24][25]. It has also been reported that the negative zeta potential shows a significant promising impact on the attachment and proliferation of the bone cells.…”
Section: Resultsmentioning
confidence: 99%
“…The determined average of zeta potential of the nanofibers was -13.5 ± 0.17 mV (Figure 3), indicating fiber stability being the repulsive charge between the fibers enough to avoid agglomeration [24][25]. It has also been reported that the negative zeta potential shows a significant promising impact on the attachment and proliferation of the bone cells.…”
Section: Resultsmentioning
confidence: 99%
“…This formulation increased the contact time between the drug and the conjunctival tissue, and thus decreased the number of administrations needed. This work showed that the concept of nanofibers in ophthalmic drug delivery is feasible [53].…”
Section: Nanofibers In Ocular Drug Deliverymentioning
confidence: 91%
“…Mirzaeei et al examined CS-based electrospun nanofibers as ocular inserts for the delivery of triamcinolone acetonide [293]. Hydrophilic fibers were prepared using CS and PVA and/or poly(vinyl pyrrolidine) and compared to hydrophobic fibers constituted of Eudragit S100 and Zein.…”
Section: Ocular Lenses and Insertsmentioning
confidence: 99%